Characterization of Manganese Oxide/Alumina Catalysts - S.A. El-Hakam (Adsorption Science & Technology)
The effect of heat treatment of manganese oxide/alumina catalysts of various manganese content on the structural and textural properties and the catalytic decomposition of hydrogen peroxide were investigated. The FT-IR results have shown that depending on the calcination temperature and metal loading MnO 2 and MnO 3 are formed on the investigated samples. No spinel structure was detected under the experimental conditions. The surface areas were found to decrease with increasing calcination temperature and metal content up to 30 wt.% Mn. The mean pore radius increased with both calcination temperature and Mn content. The rate of catalytic decomposition of H 2 O 2 was found to depend on the pH, the calcination temperature and the state of Mn on the catalyst surface.